DETERMINAN KINERJA REKSADANA SAHAM KONVENSIONAL DI INDONESIA (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
Abstract: The performance evaluation of equity mutual funds is something that needs to be considered so that investors can choose and compare mutual funds that are able to provide optimal returns. This research was conducted to determine stock selection, market timming, fund longevity, fund cash flow and fund size as factors that influence the performance of conventional equity mutual funds in Indonesia. The research sample was taken as many as 12 conventional stock mutual funds registered in the Financial Services Authority (OJK) for the period 2014-2018. The research data analysis was carried out by using multiple linear regression method. Based on hypothesis testing, it is known that only stock selection and market timming are proven to have an effect on the performance of conventional equity funds in a positive and significant direction. Meanwhile, longevity fund. fund cash flow and fund size were found to have no effect on the performance of conventional equity funds. Keywords: Mutual Fund Performance, Stock Selection, Market Timming, Fung Longevity, Fund Cash Flow, and Fund Size